PENGARUH PENGELUARAN PEMERINTAH SEKTOR KESEHATAN, PENDIDIKAN DAN INFRASTRUKTUR TERHADAP KESEJAHTERAAN MASYARAKAT DI INDONESIA - Chairati Fadliyah; Mike Triani (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
This study aims toKdetermineRtheSeffect#of government spendingQonKthe health, education and infrastructure sectors on the welfare of the people in Indonesia. TheWdata RareqsecondarykdatayingtheeformNof time series from 2015Q1 to 2017: Q4, with documentation data collection techniques and literature studies obtained from relevant institutions and agencies. The used are health sector government expenditure (X1), influence of education sector government expenditure (X2) influence of infrastructure sector government expenditure (X3) and public welfare (Y) as the dependent variable. The modelRusedWis#aGpanel model with#the#Fixed#Effect Model analysis method. The results showed that government spending in the health, education and infrastructure sectors had a positive influence on the welfare of the community with varying degrees of significance. The government expenditure that is not significant to the welfare of the community is the government#expenditure#on#health, education while the#government#expenditure on infrastructure is significant.